The perception of young adults on credibility of facebook as a source of political information and its effects towards their political behaviour / Muhammad Amir Syafiq Asri and Ismail Sualman - Asri, Muhammad Amir Syafiq; Sualman, Ismail (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2019)
Facebook has evolved from a platform of interaction and leisure, to become a major platform for political information seeking. The use of Facebook has changed and shaped people on how they consume the information, and it has been a prevalent medium for people to get and share updates about political matters. As Facebook predominantly is being used by young people, the perceived credibility of Facebook as source of political information and its influence toward their political behavior has been a main concern. The aim of this research is to identify the degree of usage of Facebook as a platform of political informationseeking among young adults, their perceived credibility and its effect toward their political behavior. It particularly examines the perceived credibility of young adults on political information on Facebook and their political behavior as of their usage and credibility’s perception. This research employed a survey method and conducted in four districts in Selangor: Shah Alam, Subang Jaya, Kuala Selangor and Kuala Langat. The sample of population comprised of 384 respondents who are young adults with age range between 18 and 30. Regression has been used by the researcher to find the relationship between Facebook usage, perceived credibility and level of political behavior. The results found that Facebook has been used by young adults as a source of political information. The results also found that political information on Facebook has been regarded as not credible and does affect on lower political behavior. The results also suggest that the more heavily usage of Facebook will eventually lead to user to perceive the information as credible.